PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN BULLYING DALAM PERSPEKTIF UNDANG-UNDANG PERLINDUNGAN ANAK: SOSIALISASI DI SMAN 5 KOTA SERANG - Ariyah Julyanti; Legita Assriyani; Rimadhani Mardhotillah; Nadia Fransisca Sagala; Khusnul Khotimah (PT. Hasba Edukasi Mandiri, 2026)
This community service activity aimed to provide an understanding of legal protection for child victims of bullying from the perspective of the Child Protection Act. The socialization was held at SMAN 5 Serang City on April 27, 2026, attended by 62 students from grades X and XI. The methods used were interactive presentations, case discussions, and question-and-answer sessions. The results showed that participants understood the forms of bullying (verbal, physical, relational, and cyberbullying), the legal basis for child protection, and criminal sanctions for perpetrators. This activity is expected to increase students' legal awareness and encourage the creation of a safe school environment free from violence.